Coal mil and bioestimulant in the formation of galphimia brasiliensis seedlings (Research, Society and Development, 2020)
Triális (Galphimia brasiliensis) is a plant originally from South America, used in landscaping. Due to its slow growth, the adoption of technologies, such as the addition of a coal mill to the substrate and the application of plant stimulants, can assist in the growth and quality of the seedlings formed. Thus, the objective of this work was to evaluate the influence of the addition of coal mill and biostimulant on the formation and quality of seedlings. The experimental design used was randomized blocks, in a 5x2 factorial scheme, testing proportions (0%; 7.5%; 15%; 22.5% and 30%) of coal mill added to a commercial substrate, in the presence (25 mL L-1) or absence of plant biostimulant, with four repetitions. The parameters were analyzed: height, length of root, leaf area, diameter of neck and dry mass of root, aerial part and total. Based on these parameters, the quality of the seedlings was evaluated by the relationships: height / diameter (RHD), aerial part / root (RPAR), height / aerial part (RHPA) and the Dickson Quality Index (IQD). The combined use of coal mill and biostimulant influenced only the production of dry root mass of the plants of G. brasiliensis. The addition of biostimulant did not influence the formation and quality of G. brasiliensis seedlings. The coal mill added to the substrate in proportions varying from 12.2 to 13.4% provided an increase in the height of the seedlings, in the dry mass of root and total. Increasing proportions after 18.6% of coal grinding, in the tested interval, had an increase in the aerial part and root ratio and in Dickson's quality index.